The numerical simulation of nanosecond-pulsed discharge-assisted ignition in lean-burn natural gas HCCI engines - Ban, Yangyang; Zhang, Fan; Zhong, Shenghui; Zhu, Jiajian (Frontiers in Mechanical Engineering, 2022)
A plasma assisted internal combustion engine model is established based on detailed plasma kinetics, combustion kinetics and physical compression/expansion processes. The effects of nanosecond repetitively pulsed discharge (NRPD) on plasma-assisted ignition characteristics of mixtures under different fuel concentrations are studied in HCCI engine relevant conditions. The coupled plasma and chemical kinetic model are validated with experiments. The comparison between NRPD and thermal ignition with a certain amount of input energy is carried out and the results show that the former can ignite mixture owing to the kinetic effect of nonequilibrium plasma, but the latter cannot ensure ignition. Path flux analysis shows that excited states and electrons react with fuel providing O and H directly, increasing the possibility of ignition at low temperature. The effect of NRPD on combustion performance under various equivalence ratios (φ) is investigated. It is found that in ICEs with NRPD the ignition delay time at lean-burn condition (φ = 0.5) is the shortest one among three demonstrative cases. Even though, the leaner mixture case with φ = 0.2 is more favorable for the production of O and OH during the discharge. After discharge, the heat release in case 2 with φ = 0.5 dramatically increase resulting in the temperature exceeding that in ultra-lean case. As the piston moves up, the higher amounts of CH3, HO2 and H2O2 as well as higher temperature for lean-burn (φ = 0.5) case lead to the rapid increase of OH and O which accelerates the consumption of methane and finally the earliest hot ignition near TDC. Finally, a series of parameter studies are performed to show the effects of E/N, current density, φ and discharge timing on ignition process. The results suggest that discharge parameters E/N and current density together with discharge timings and equivalence ratios can improve ignitability in internal combustion engines.